Ayurvedic management of acute viral hepatitis: A case report (Indian Journal of Case Reports, 2018)
Acute viral hepatitis (AVH) has resemblance with Kamala mentioned in Ayurveda. Kamala is a disease of the Raktavaha srotas (a system which includes liver, spleen, blood vessels, and reticuloendothelial tissue) and dominant of pitta dosha. Nitya virechana (regular use of mild laxative) and Pitta samana is the principles to treat the condition in Ayurveda. Here, we report the case of a 20-year-old male diagnosed with AVH treated in accordance to the Ayurvedic principles reported, that is, Mridu virechana (regular use of mild laxatives), and Pitta samana. The total duration of the treatment including follow-up was 60 days. A complete remission of symptoms with a substantial reduction in bilirubin and hepatic enzymes observed following Ayurvedic treatment. Hence, presenting this case is an evidence to demonstrate the effectiveness of Ayurvedic treatment in AVH.